2013
DOI: 10.1371/journal.pone.0066991
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density, Bone Turnover Markers and Fractures in Patients with Systemic Sclerosis: A Case Control Study

Abstract: ObjectiveThe aim of our study was to elucidate the pathophysiology of systemic sclerosis-related osteoporosis and the prevalence of vertebral fragility fracture in postmenopausal women with systemic sclerosis (SSc).MethodologyFifty-four postmenopausal women with scleroderma and 54 postmenopausal controls matched for age, BMI, and smoking habits were studied. BMD was measured by dual energy-x-ray absorptiometry at spine and femur, and by ultrasonography at calcaneus The markers of bone turnover included serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 27 publications
11
59
0
12
Order By: Relevance
“…However, the relationship between skin involvement and BMD remained uncertain 17 31. Also, previous studies failed to find significant associations between other factors and OF in SSc patients 12 13. Several risk factors for OF, such as propensity of falls, family history of OF, calcium and vitamin D intake, alcohol consumption and smoking status, were also unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between skin involvement and BMD remained uncertain 17 31. Also, previous studies failed to find significant associations between other factors and OF in SSc patients 12 13. Several risk factors for OF, such as propensity of falls, family history of OF, calcium and vitamin D intake, alcohol consumption and smoking status, were also unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, Carmel et al reported no correlation between antivitamin D antibodies and some clinical features [18]. Acute-phase reactant including C-Reactive Protein (CRP) and Erythrocyte Sedimentation Rate (ESR) were extensively investigated in some studies reviewed [11][12][13][14]. Serum calcium, phosphate and bone turnover metabolism were mostly measured in those papers having BMD or parathyroid hormone (PTH) determination in their study protocol [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Manifold data [9][10][11][12][13] have been provided about the association between low Vitamin D serum levels and clinical features of disease, but few evidences were found to be concordant. Since understanding the pathogenesis implies advances in therapeutic strategies, it is a need to draw conclusions about the role, true or fake, of the hormone, in promoting the onset of SSc.…”
Section: Introductionmentioning
confidence: 99%
“…Bone densitometry utilizing DXA is the most widely used Systemic sclerosis 22% to 60% (spine or hip) (24,25) Systematic vasculitis 14.9% to 85% (spine or hip) (26,27) Juvenile rheumatic diseases 38.7 to 60% (spine or hip) (28)(29)(30) quantitative technique in clinical practice, and remains the gold-standard test for the osteoporosis diagnosis and quantification. Of all modalities, it has the most data on predicting fractures in post-menopausal women in longitudinal population-based studies (41).…”
Section: Dxamentioning
confidence: 99%